Intracellular expression of granzymes A, B, K and M in blood lymphocyte subsets of critically ill patients with or without sepsis - García-Laorden, MI; Hoogendijk, AJ; Wiewel, MA; van Vught, LA; Schultz, MJ; Bovenschen, N; de Vos, AF; van der Poll, T (Oxford University Press, 2021)
Sepsis is a complex syndrome related to an infection-induced exaggerated inflammatory response, which is associated with a high mortality. Granzymes (Gzm) are proteases mainly found in cytotoxic lymphocytes that not only have a role in target cell death, but also as mediators of infection and inflammation. In this study we sought to analyse the intracellular expression of GzmA, B, M and K by flow cytometry in diverse blood lymphocyte populations from 22 sepsis patients, 12 non-infected intensive care unit (ICU) patients and 32 healthy controls. Additionally, we measured GzmA and B plasma levels. Both groups of patients presented decreased percentage of natural killer (NK) cells expressing GzmA, B and M relative to healthy controls, while sepsis patients showed an increased proportion of CD8+ T cells expressing GzmB compared to controls. Expression of GzmK remained relatively unaltered between groups. Extracellular levels of GzmB were increased in non-infected ICU patients relative to sepsis patients and healthy controls. Our results show differential alterations in intracellular expression of Gzm in sepsis patients and non-infected critically ill patients compared to healthy individuals depending on the lymphocyte population and on the Gzm.